The Effect of Mindfulness Practices on Learning Anxiety: A Case Study on High School Students - Deswi Metasari; Ayu Andriyaningsih; Burmansah Burmansah; Eko Pramono; Juni Suryanadi; Rini Kasrah; Wistina Seneru (Universitas Sebelas Maret, 2024)
The purpose of this study was to examine the effect of mindfulness practice on students' learning anxiety. Students often face problems such as a lack of understanding of the material presented during lessons and difficulty completing assignments. This study uses a quantitative approach, using a survey method. The population consists of 118 students, with a sample of 81 respondents selected through Proportional Random Sampling. The study was conducted on high school students in the 2024/2025 academic year. The study showed a significant favorable influence between mindfulness practices and learning anxiety, with a t-value of 7.303 and a significance level of 0.000 (<0.05). Simple regression analysis produced an R-squared value of 0.375, indicating that mindfulness practices explain 37.5% of the variation in learning anxiety, while other factors influence the remaining 62.5%.